Prospective, non-randomized, 36-month study of second-generation trabecular micro-bypass stents with phacoemulsification in eyes with various types of glaucoma - Hengerer, Fritz; Auffarth, Gerd U.; Riffel, Christopher; Conrad-Hengerer, Ina (Ophthalmology and therapy, 2018)
IntroductionThe aim of this study was to assess 36-month outcomes after cataract surgery and implantation of two second-generation trabecular micro-bypass stents (iStent inject, Glaukos Corporation, San Clemente, CA, USA) into eyes with predominantly primary open-angle glaucoma (POAG) or pseudoexfoliative glaucoma (PEX).MethodsThis prospective, non-randomized, consecutive cohort study included eyes with POAG (n = 60), PEX (n = 15), appositional narrow-angle (n = 4), pigmentary (n = 1), or neovascular (secondary) (n = 1) glaucoma and cataract requiring surgery. All eyes (n = 81) underwent ab interno iStent inject implantation following cataract surgery. Effectiveness endpoints through 36 months included intraocular pressure (IOP), number of medications, and proportion of eyes with ≥ 20% IOP reduction, IOP ≤ 18 mmHg, and IOP ≤ 15 mmHg. Safety measures included corrected distance visual acuity (CDVA), adverse events, and secondary surgeries. Outcomes were evaluated for the overall cohort, and for the POAG and PEX subgroups.ResultsPreoperatively, 32.1% of eyes had undergone prior glaucoma surgery, 56% were on 3-4 medications, and 1 eye (1%) was medication-free. At 36 months postoperatively, mean IOP reduced by 37% (14.3 ± 1.7 mmHg versus 22.6 ± 6.2 mmHg preoperatively), and mean medication burden decreased by 68% (0.8 ± 0.9 versus 2.5 ± 1.1 medications preoperatively). IOP reduced by ≥ 20% in 78% of eyes; 100% of eyes reached IOP ≤ 18 mmHg and 71% reached ≤ 15 mmHg. Medication burden reduced considerably: 22 eyes (54%) were medication-free compared to 1 eye (1%) preoperatively; 1 eye (2%) required ≥ 3 medications compared to 45 eyes (56%) preoperatively; and 92.7% of eyes required reduced medications postoperatively. From 3 through 36 months, mean IOP remained ≤ 15.0 mmHg, and mean number of medications remained ≤ 0.9. Outcomes in the POAG and PEX subgroups included 33% and 32% lower IOP, and 68% and 64% fewer medications, respectively. iStent inject showed a favorable safety profile, including no intraoperative complications, minimal adverse events, and a stable CDVA.ConclusionThis real-world cohort of eyes with various types of glaucoma and considerable disease burden exhibited durable and safe IOP and medication reductions through 36 months following iStent inject implantation with cataract surgery. Outcomes were similarly beneficial in eyes with POAG and PEX.FundingArticle processing charges were funded by Glaukos Corporation (San Clemente, CA, USA).
First Online: 14 November 2018
Gesehen am 02.10.2019